Physical foundations of technical acoustics - Malecki, Ignacy (Pergamon Press, 1969)
Physical Foundations of Technical Acoustics discusses theoretical foundations of acoustical engineering. It is not so much a technical compendium as a systematic statement of physical laws so conceived that technologists might find in it all the information they need to become acquainted with the physical meaning and mathematical expression of phenomena they encounter in their work. To facilitate the acquirement of notions, which lie beyond a layman's grasp, the plan of narration adopted consists in beginning with the simplest idealized cases and then gradually moving on to the truest possibl.